Reliability of a consensus-based ultrasound score for tenosynovitis in rheumatoid arthritis. Issue 8 (14th September 2012) - Naredo, Esperanza; D'Agostino, Maria Antonietta; Wakefield, Richard J; Möller, Ingrid; Balint, Peter V; Filippucci, Emilio; Iagnocco, Annamaria; Karim, Zunaid; Terslev, Lene; Bong, David A; Garrido, Jesús; Martínez-Hernández, David; et al.
Abstract : Objective: To produce consensus-based scoring systems for ultrasound (US) tenosynovitis and to assess the intraobserver and interobserver reliability of these scoring systems in rheumatoid arthritis (RA). Methods: We undertook a Delphi process on US-defined tenosynovitis and US scoring system of tenosynovitis in RA among 35 rheumatologists, experts in musculoskeletal US (MSUS), from 16 countries. Then, we assessed the intraobserver and interobserver reliability of US in scoring tenosynovitis on B-mode and with a power Doppler (PD) technique. Ten patients with RA with symptoms in the hands or feet were recruited. Ten rheumatologists expert in MSUS blindly, independently and consecutively scored for tenosynovitis in B-mode and PD mode three wrist extensor compartments, two finger flexor tendons and two ankle tendons of each patient in two rounds in a blinded fashion. Intraobserver reliability was assessed by Cohen's κ. Interobserver reliability was assessed by Light's κ. Weighted κ coefficients with absolute weighting were computed for B-mode and PD signal. Results: Four-grade semiquantitative scoring systems were agreed upon for scoring tenosynovitis in B-mode and for scoring pathological peritendinous Doppler signal within the synovial sheath. The intraobserver reliability for tenosynovitis scoring on B-mode and PD mode was good (κ value 0.72 for B-mode; κ value 0.78 for PD mode). Interobserver reliability assessment showed good κ values for PD tenosynovitis scoring (first round, 0.64; second round, 0.65) and moderate κ values for B-mode tenosynovitis scoring (first round, 0.47; second round, 0.45). Conclusions: US appears to be a reproducible tool for evaluating and monitoring tenosynovitis in RA.